Volumetric Brain Loss Correlates With a Relapsing MOGAD Disease Course - Rechtman, Ariel; Brill, Livnat; Zveik, Omri; Uliel, Benjamin; Haham, Nitzan; Bick, Atira S.; Levin, Netta; Vaknin-Dembinsky, Adi (Frontiers in Neurology, 2022)
Background: Myelin oligodendrocyte glycoprotein antibody disorders (MOGAD) have evolved as a distinct group of inflammatory, demyelinating diseases of the CNS. MOGAD can present with a monophasic or relapsing disease course with distinct clinical manifestations. However, data on the disease course and disability outcomes of these patients are scarce. We aim to compare brain volumetric changes for MOGAD patients with different disease phenotypes and HCs. Methods: Brain magnetic resonance imaging (MRI) scans and clinical data were obtained for 22 MOGAD patients and 22 HCs. Volumetric brain information was determined using volBrain and MDbrain platforms. Results: We found decreased brain volume in MOGAD patients compared to HCs, as identified in volume of total brain, grey matter, white matter and deep gray matter (DGM) structures. In addition, we found significantly different volumetric changes between patients with relapsing and monophasic disease course, with significantly decreased volume of total brain and DGM, cerebellum and hippocampus in relapsing patients during the first year of diagnosis. A significant negative correlation was found between EDSS and volume of thalamus. Conclusions: Brain MRI analyses revealed significant volumetric differences between MOGAD patients and HCs, and between patients with different disease phenotypes. Decreased gray matter volume during the first year of diagnosis, especially in the cerebrum and hippocampus of MOGAD patients was associated with relapsing disease course.